#TITLE_ALTERNATIVE# - Benny Purwanto (NIM: 13206126) Pembimbing : Prof. Dr. Ir. Bambang Riyanto T., M.Sc, Vinsensius
Active Noise Control System is one of the noise cancellation method by using antinoise signal produced by the system to cancel the noise from the noise source. The antinoise signal generated should have a reversed in phase with the noise in order to cancel the noise. The active noise control system is effective to cancel the low frequency noise. That is the advantage of using the ANC system rather than pasive noise control. The pasive noise control needed to cancel the low frequency noise can cost a bigger price. The implementation of ANC system should consider some important factors, such as: sensor and antinoise source placement, algorithm, noise character and quiet zone. The experiment has a purpose to cancel the noise generated from an industrial machine which come from some point and has a broadband frequency characteristic in the open space. It will be done by using Filtered Error LMS Algorithm with geometry variation. The experiment is also done using single channel and multichannel ANC system in laboratory and factory where the machine is located. There will be some parameter considered during the experiment, such as: filter order, geometry, quite zone, sampling frequency, pasive cancellation, and additional component. The result shows that the noise is reduced about 1 dBA around the error sensor with the experiment using DSK TMS320C6713 together with DSK_AUDIO16_BASE and DSK_AUDIO4 for single channel ANC and 1x4x4 Decentralization ANC. The noise reduction can reach 4,15 dBA while using the single channel FELMS algorithm without using DSK_AUDIO16_BASE and DSK_AUDIO4. The other important result is that the sensor and antinoise souce placement, sampling frequency and filter order play the important role to increase the noise reduction.